Disgresionario poético - Mesa del Olmeda, active 16th century; Martínez Berriochoa, Alejandro (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert Verlag, 2018)
Unpublished treatise on poetry. Divided into six "digresiones," each further divided into "paradojas." Contains numerous quotations from and references to other poets and writers. Fol. 1 (as numbered) contains a "Catalogo de los escritores y philosophos con otros autores de quien se ha aprouechado el autor de este volumen," which lists alphabetically ca. 500 authors ranging from the poets of antiquity and the Fathers of the Church to writers of the late 16th century. The list does not include Lope de Vega, which suggests that the manuscript was written before ca. 1615. This treatise was probably intended to be printed; at the end there is an "aprobación" signed by Don Alonso de Ercilla. Cf. Díez Fernández for further discussion of contents and authorship.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed April 30, 2019)
Keywords: Spanish poetry -- Classical period, 1500-1700 -- History and criticism -- Early works to 1800.; Spanish poetry -- Classical period, 1500-1700 -- Classical influences -- Early works to 1800.; Ottava rimas, Spanish; Poetics -- Early works to 1800.; Poets, Spanish -- Classical period, 1500-1700.; Manuscripts, Spanish; Manuscripts -- Spain -- Alcalá de Henares; Electronic books